Pengaruh Current Account Saving Account Terhadap Profitabilitas Pada Bank Muamalat Indonesia Periode 2021-2025 - Ellina Rahmah; Nurlaila Safira; Yani Aguspriyani (Sharing: Journal of Islamic Economics Management and Business, 2026)
A large proportion of Current Account Savings Account (CASA) balances can help banks reduce their cost of funds and potentially increase profits. This study examines the effect of CASA on profits, as measured by Return on Assets (ROA) at Bank Muamalat Indonesia. This study used a quantitative approach, utilizing secondary data in the form of Bank Muamalat Indonesia's quarterly financial reports for the 2021-2025 period, resulting in 20 observation units (5 years × 4 quarters). Sampling was conducted using purposive sampling with the criteria of the availability of official quarterly financial reports during the study period. Data processing was performed using simple linear regression using Stata software and tested using the classical assumption test. The findings indicate a negative relationship between CASA and ROA with a regression coefficient of -0.0024243, although it is not statistically significant at the 5% significance level (p = 0.084). This means that a high proportion of CASA does not always directly contribute to increased bank profitability, as it is also determined by other factors such as operational efficiency and productive fund management.